Organizational Culture and Performance of SMEs in Uganda: A Case study of Hotel Sector - Aketch, Everline; Basheka, Benon C.; Bagire, V. (International Journal of Technology and Management, 2017)
The purpose of the study was to establish the effect of organizational culture on the performance of SMEs in Uganda. A cross-sectional survey design was used to collect data from 112 hotels in Eastern part of Uganda. Out of which Ninety-six (96) hotels were retain for analysis. This study unlike majority of other studies included both managers and employees as participants. Denison cultural dimensions of involvement, consistency, adaptability and mission were used. Reliability of all the variables was tested using Cronbach’s alpha(α) for inter-item consistency reliability and specifically for organizational culture was established to be at α=0.92 The analysis of results confirmed that organizational culture positively influenced performance of SMEs by 12.4%. The organizational culture aspects that had significant effect on performance were found to be mission (β=0.329, sig=0.006) and involvement (β= 0.208, sig=0.042) traits. Consistency (β=0.120, sig=0.467) and adaptability (β=0.120, sig=0.181) traits were found to insignificant contributors to performance of SMEs. The study recommends that management encourages proactive involvement of employees in the decision making process and in addition particular attention should be paid to the process of strategic planning. The research was limited to one sector therefore future studies should consider studies in other sectors.
Keywords: Organizational culture, Involvement, Consistency, Adaptability, Mission, SMEs and Performance